Preparation of high Fischer ratio peptides from seabuckthorn (Hippophae rhamnoides L.) seed meal, characterization and functional evaluation - Yuanju Zheng; Yunxi Zhou; Yichao Pei; Zhuoling Feng; Michael Yuen; Hywel Yuen; Qiang Peng (Food Chemistry: X)
In order to study the changes before and after the preparation of high F-ratio peptides, seabuckthorn seed meal high F-ratio peptides (HFP) were prepared by using alkaline protease and papain with activated charcoal adsorption, which resulted in an F-ratio of 21.626 at a peptide yield of 22.54 ± 0.86 %. A comparison of seabuckthorn seed meal peptides (HP) and their high F-ratio counterparts revealed alterations in the secondary structure of the peptides, a decline in fluorescence intensity. Additionally, a shift in the microstructure towards a more loosely packed configuration was observed. Sensory evaluation yielded no significant differences. The physicochemical properties of the peptides were enhanced, and their solubility was improved. Conversely, the emulsification and foaming abilities of the peptides were reduced. The functional activities of the peptides, such as antioxidant and antiglycemic properties, were also enhanced. This study provides a reference for the utilization of high F-ratio peptides in food applications.